The Ideology Translation, Gender and Readability of Barbie Stories (Global Scientific Review, 2023)
The research aims to analyze the translation ideology and its impact on the translation results. The method used is document analysis. The research flow is that the researcher reads the English source language text into the Indonesian translation text, then the researcher looks for direct sentences from the text using ideological translation. The result of the research is that Barbie as Island Princess has an ideology translation of romance while Barbie a Baby Doctor has an ideology translation of determination, desire and professional responsibility. This Research conducted analysis feminist and Gender Characteristics on Barbie Stories with domestication Ideology. The benefit of research is scientific development in the field of translation.